The Semiotics of Gold Flexing on Social Media: A Peircean Analysis of Tiktok - Setyowati, Ratini; Setiawati, Beta; Murti Wardhani, Evi (LPPM Universitas Duta Bangsa Surakarta, 2024)
Tik Tok is a popular platform for people to influence other by sharing status or short-form videos. the purposes of this study is to explore how visual signs, such as gold jewellery and other luxury items, are utilized in the context of flaunting wealth, and how meanings related to wealth and social status are conveyed and understood by employing the elements of Charles Sanders Peirce's semiotics. The method of the study is a qualitative method with a descriptive approach. Semiotic analysis is used to analyze captions, video transcripts, videos, post images, and the interpretation of the messages conveyed in the images from the TikTok account @mirahayati91. The result of the study shows that the elements of Charles Sanders Peirce's semiotics comprises three main elements that can be applied to analyse signs within a given content, including the gold flaunting content on Mira Hayati's TikTok account. The videos posted on @mirahayati91 attract significant public attention, as each upload elicits responses from online communities, resulting in both positive and negative comments. This dynamic showcases how Mira Hayati’s portrayal of wealth sparks diverse reactions, reflecting broader societal views on success, luxury, and social status. The conclution is Through semiotic analysis, the researcher successfully revealed the meanings behind the images and videos uploaded on the TikTok account @mirahayati91.